The Secrets and Silences of Edith Wharton's Women - Parsons, Isabelle. author. (orcid)0009-0009-3804-1151 Link aut Link
XIII, 221 p. 7 illus., 6 illus. in color.
Keywords: “Isabelle Parsons’ eloquent study offers a valuable new contribution to our understanding of Wharton’s deployment of the themes of secrets and silence in both her fiction and non-fiction, notably in their application to female protagonists and their social realities. The book is a welcome, rewarding and timely addition to a vibrant period of Wharton scholarship.” —Laura Rattray, Reader in American Literature, University of Glasgow, UK “With remarkable care and insight, Parsons beautifully unfolds the complexity of secrets and silences in Wharton’s work and proves that ‘Wharton’s writing about women is a doorway into the issues of our day’. Nuanced, rigorous, and extensive, Parsons’ book is an important contribution to Wharton scholarship as well as gender and women’s studies.” —Myrto Drizou, President of the Edith Wharton Society and Associate Professor of English, Nord University, Norway “To her thorough familiarity with Wharton scholarship Parsons adds strategic archival research to bring new critical insights into Wharton’s texts from the well-known to the under-appreciated. Her study traces Wharton’s multi-valenced approach to women’s silences and secrets revealing how they reflect female oppression as much as women’s bid for power.” —Rita Bode, Professor of English Literature, Trent University, Canada and Editor, Edith Wharton Review Edith Wharton’s sensitively observed portraits of women’s lives a century ago resonate into the present day, captivating readers now as they did then. Threaded throughout her accounts is a rich seam of secrets and silences that reveals Wharton’s keen grasp of the realities navigated by women, and her astute use of withholding to tell their stories. This book explores her frequent marshalling of secrets and silences, presented as an integral part of her literary aesthetic, to cast light on her enduring interest in women’s experiences in private and public settings during the early twentieth century. Isabelle Parsons is an honorary associate in the Department of English and Creative Writing at The Open University, UK, where she also tutors English literature. She has published scholarly articles on the works of Edith Wharton.